Experimental characterization of interlaminar fracture toughness of composite laminates assembled with three different carbon fiber lamina (Fracture and Structural Integrity, 2017)
In the present work, the fracture resistance of a carbon fiber composite under mode I and mode II loading have been experimentally determined. For the mode I and II, the energy release rate G has been determinate for each material. In some cases, only a single estimation of G was possible due to problems in the propagation such as extensive fiber bridging and loss of planarity of the running crack. The experimental results relative to DCB tests have been analyzed in order to derive statistical trends. Only the samples for which more than three crack advance data points have been collected are considered in the analysis. The G values are those obtained with the compliance calibration method (CC). For ENF test, determination of critical GII, in addition to the value calculated with the relationship given in the prescription EN6034, other two values, the non linear and visual non linear, are also given. The crack propagation resulted to be unstable for all specimens tested and only a single value of GII could be determined.
Keywords: Carbon fiber; Delamination; ENF; DCB